O ensino superior noturno no Brasil: história, crescimento e políticas públicas no início do século XXI - Terribili Filho, Armando; Barreiro, Iraide Marques de Freitas [UNESP] (My University, 2013)
There are three distinct and complementary objectives The first objective is to present a short historical overview on the establishment of evening courses in Brazil (classes are held on weekdays, generally from 7:00 pm to 10:30 pm), including those in the higher education level, occurred on the middle of last century. The second objective is to demonstrate the growth of evening higher education, considering that in 1998, of the 2.1 million college enrollments, 55.3% were enrolled in evening courses; in 2010, twelve years later, of the 5.4 million students enrolled, there were 63.5% enrolled in evening courses. The third objective is to discuss current public policies to expand evening openings in public institutions which represent nowadays only 16.1% of the 3.4 million enrollments for evening classes. In the third objective it is included the discussion of programs for scholarships and tuition loans. The research results pointed to the importance of federal programs for scholarships and tuition loans for students from private institutions such as the 1,382,484 scholarships since 2004 (PROUNI Program) and the 847,000 tuition loans since 1999 (FIES Program). Important steps have been made by the Brazilian government. Considering that there are 3,987,424 enrollments in private institutions, the effectiveness of the programs for scholarships and tuition loans is still insufficient to meet the universal benefits for the student’s needs. Evening courses became the real instrument of social inclusion for many Brazilian youths and must be expanded quantitatively and qualitatively, with aggressive public policies, including also, scholarships and tuition loans.

Este artigo tem três objetivos distintos e complementares. O primeiro é efetuar um rápido resgate histórico da criação do ensino noturno no país, incluindo o ensino superior, fato ocorrido em meados do século passado. O segundo, pôr em evidência a expansão do ensino superior noturno, pois, em 1998, dos 2,1 milhões de estudantes do ensino superior em cursos de graduação presenciais, 55,3% estavam matriculados no período noturno; em 2010, 12 anos depois, dos 5,4 milhões de estudantes do ensino superior, o índice no período noturno é de 63,5%. O terceiro objetivo é debater as atuais políticas públicas para expansão de vagas no período noturno em instituições públicas, que hoje representam apenas 16,1% das 3,4 milhões de matrículas em cursos noturnos. Os resultados da pesquisa apontaram a importância de programas federais para a concessão de bolsas de estudo e de empréstimos para estudantes de instituições privadas, como as bolsas de estudo (desde 2004, 1.382.484 estudantes foram atendidos pelo PROUNI) e os 847.000 empréstimos pelo FIES (desde 1999). O governo brasileiro tem dado passos importantes. Considerando que há 3.987.424 matrículas em instituições privadas, a eficácia dos programas de bolsas de estudo e de empréstimos para pagamento de mensalidades ainda é insuficiente para atender às necessidades universais do estudante. O ensino superior noturno se tornou, no país, um instrumento de inserção social que precisa ser expandido de forma quantitativa e qualitativa, com políticas diferenciadas.
Higher education in night courses in Brazil: history, growth and public policy at the beginning of the XXI century
Keywords: Higher education; Evening higher education; Evening education; Public policy; Educational policy; Educação superior; Ensino superior noturno; Ensino noturno; Políticas públicas; Políticas educacionais